INFORMAR E ENTRETER: O PROCESSO DE PRODUÇÃO DA NOTÍCIA NO HOJE EM DIA - ENDO, BARBARA (2016)
The entertainment is embedded in everyday life of modern society in a way that goes beyond just the moments of leisure and entertainment, becoming present in professional environments, education and information. Amid this new design, the Communication also realizes changes, as the interactivity promoted by the media coverage, the new appearance of the audience, more demanding and connected, or the hybridization of genres and formats. In this context, there are entertainment programs, especially in the television, incorporating technical and practical aspects of journalism, including the narrative and production processes. Such programs convey a content called infotainment, which combines information and entertainment and thus the journalistic representation of social life is linked to distraction and fun. The dissertation analyzes the content of the news production process within an entertainment program and varieties that features lots of news content in its composition: the Hoje Em Dia, from Rede Record. This is a qualitative study, study type of case, using direct observation techniques, semi-open interviews, desk research and content analysis. The issue of technical reproducibility standards and the inclusion of everyday elements combined with the cultural industry and mass communication is also depicted in this dissertation. The main intention is to understand how the dynamics of journalistic production programs to entertain and at the same time inform. How these hybrid products of modernity are thought and how infotainment theory can be combined with the communicational mediations of culture